2007
DOI: 10.1007/s11661-007-9400-6
|View full text |Cite
|
Sign up to set email alerts
|

A Convective Heat-Transfer Model for Partial and Full Penetration Keyhole Mode Laser Welding of a Structural Steel

Abstract: In the keyhole mode laser welding of many important engineering alloys such as structural steels, convective heat transport in the weld pool significantly affects temperature fields, cooling rates, and solidification characteristics of welds. Here we present a comprehensive model for understanding these important weld parameters by combining an efficient keyhole model with convective three-dimensional (3-D) heat-transfer calculations in the weld pool for both partial and full penetration laser welds. A modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 39 publications
1
53
0
1
Order By: Relevance
“…Few studies have been reported on the mechanisms that are responsible for the shape of weld bead profiles [54][55][56]. The effect of surface deformation and melt flow on weld bead formation was first investigated by Bradstreet [57] when correlated the bead profile of a convex-shaped profile to the surface tension, which controls edge wetting in the weld pool.…”
Section: Metallography and Visual Examinationmentioning
confidence: 99%
“…Few studies have been reported on the mechanisms that are responsible for the shape of weld bead profiles [54][55][56]. The effect of surface deformation and melt flow on weld bead formation was first investigated by Bradstreet [57] when correlated the bead profile of a convex-shaped profile to the surface tension, which controls edge wetting in the weld pool.…”
Section: Metallography and Visual Examinationmentioning
confidence: 99%
“…It can be noted that the right hand side of this advection-diffusion equation is both time and space averaged. Equation (21) corresponds to the conservation equation energy for a specific added metal and energy rates. In the numerical resolution, Eq.…”
Section: Implementation In Conservation Equationsmentioning
confidence: 99%
“…Lastly, buoyancy forces can no longer be neglected since it has been proved they have a great influence in horizontal GTA welding [17]. Because of the improvements in hybrid welding modelling and the research focus on keyhole phenomenon, these numerical methods have been carried over to laser/GMAW modelling [18,19,20,21,22]. As a result, the numerically obtained bead shapes better fit the experimental ones.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16]. Mathematical and numerical models usually describe chosen phenomena, due to the computational complexity of the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical and numerical models usually describe chosen phenomena, due to the computational complexity of the problem. Therefore, coupled thermal phenomena and phase transformations in solid state are usually ignored in numerical analysis of welding processes [5,8,9,15,16]. However, latent heat generated during phase transformations in heat treatment of steel influences temperature distribution and has a significant effect on numerically predicted microstructure composition [17,18].…”
Section: Introductionmentioning
confidence: 99%